14. (7-2) Solve the system using substitution. 15. (7-4) Solve the system using elimination. \( \begin{array}{c}4 x+3 y=-2 \\ x+5 y=-9 \\ 3 x+3 y=-15 \\ 5 x-9 y=3\end{array} \)
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
The Deep Dive
To solve the system using substitution for the equations \(4x + 3y = -2\) and \(x + 5y = -9\), start by isolating one variable. From the second equation, you can express \(x\) as \(x = -9 - 5y\). Plug this value for \(x\) into the first equation, leading you to solve for \(y\). Once \(y\) is found, substitute back to determine \(x\). For the elimination method using the equations \(3x + 3y = -15\) and \(5x - 9y = 3\), first, simplify the first equation to get \(x + y = -5\). Next, manipulate both equations so that when added or subtracted, one of the variables cancels out. This will allow you to find one of the variables easily before substituting back to find the other. Enjoy the numerical dance!